GENOMIC LOCI THAT INFLUENCE BLOOD PRESSURE: USING HAPLOTYPE ANALYSIS AND 1000 GENOMES PROJECT DATA TO INTEGRATE ASSOCIATION FINDINGS FROM LOCAL POPULATION STUDIES. (June 2018) - Gallo, J.; Ochoa, J.; Misas, E.; Bedoya, G.; Parati, G.; Aristizabal, D.; McEwen, J.; Clay, O.
Abstract : Objective: Studies and metastudies of the past decade have found human genes or loci reproducibly associated with elevated blood pressure (BP) levels and/or risk of cardiovascular disease. Confirmed associations of systolic (S) and diastolic (D) BP levels with genetic variation at individual SNPs have also been repeatedly reported, but with modest effect sizes (< 2 mmHg/allele). We explored the use of population haplotype analysis methods in order to better understand association findings focusing on BP levels. Figure. No caption available. Design and method: We used available and originally derived methods for analyzing association evidence and haplotype data in a cohort of individuals from Medellín, Colombia (n = 357), which we integrated with public data from 1000 Genomes (n = 2, 504). Genotyping at different loci previously reported to be associated with BP levels or cardiovascular disease, including 67 SNPs from 9p21.3, was performed. Conventional SBP and DBP levels were measured and defined by the average of four conventional sitting BP measurements made at five min intervals by two trained physicians. Ambulatory BP monitoring (ABPM, Mobil-O-Graph NG, IEM, Stolberg, Germany) was performed and mean SBP and DBP were averaged for the day, night and 24-hour periods. Results: The loci we analyzed showed a marked tendency: haplotypes at a given locus (from one of the two homologous chromosomes) consisted mainly of few (5 or less) distinct, easily distinguishable multi-SNP motifs (see Figure, or Gallo et al., 2017, JACC 70:1539–1540) that mostly recur across the world's populations. Consistent associations were found either for conventional or ambulatory BP levels in several loci, in particular in 9p21.3. Conclusions: Although marked haplotype-block structures have been noted before, association studies have only very rarely incorporated them into their methods. The variation at the SNPs observed in our study consists largely of variation among haplotype classes, modulated by local point mutations within classes. For instance, the results for 9p21.3 show how haplotype methods can help understanding and interpreting SNP-by-SNP variation and associations. These results would be compatible with the hypothesis that elevated BP levels could be one of the mechanisms by which genetic variation in 9p21.3 increases risk of cardiovascular disease.